2015 IEEE International Conference on Robotics and Automation (ICRA) 2015
DOI: 10.1109/icra.2015.7139797
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of effect of fingertip stiffness on resistible force in grasping

Abstract: Abstract-In this study, we experimentally investigated the effect of robot fingertip stiffness on the maximum resistible force. The maximum resistible force is defined as the maximum tangential force at which the fingertip can maintain contact when applying and increasing tangential/shearing force. We include in the definition of this term the effect of fingertip deformation. In contrast to our previous study [11], cylindrical fingertips with flat surfaces were used in this study so that the contact area would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…15. These results correspond to our previous results, which showed that stiffer fingertips have a higher resistible force (frictional force) [11], [12].…”
Section: B Results and Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…15. These results correspond to our previous results, which showed that stiffer fingertips have a higher resistible force (frictional force) [11], [12].…”
Section: B Results and Discussionsupporting
confidence: 81%
“…Watanabe et al [10], [11], [12] investigated the effects of fingertip stiffness on the grasping stability by performing experiments. These studies focused on the contact between rigid objects and soft fingers.…”
Section: A Related Workmentioning
confidence: 99%
“…These four parts are connected with a fitting. The silicone part played a key role acting as a spring, and was made of silicone: KE-1308 and hardener (volume: 6 %): CAT1300L-3 (Shin-etsu Silicone, see [22], [23] for details on the stiffness information; Fig. 17 (a) shows the material information for the relationship between the load and displacement).…”
Section: Structure and Principlementioning
confidence: 99%
“…In other words, the pushing distance/force at the danger area starting point is the guaranteed maximum (grasping) force that can avoid fracture. In addition, a phase change from Phase 1 to Phase 2 indicated an alteration in the tofu (it became hard), and there have been reports that a harder contact area can produce larger frictional forces when contacting soft materials [18,19]. Therefore, easier grasping can be expected compared to previous phases.…”
Section: Danger Area Starting Point For Avoiding Fracture and Delmentioning
confidence: 99%